Identification of Vibration Parameters in a Spacecraft using Kalman Filters, Numerical Search and Phase-Locked Loops - Aage Skullestad (Modeling, Identification and Control, 2000)
Communication in space requires antennas that are accurately pointed. Often antennas are mounted on lightly damped space structures, that are easily set into vibration, which decreases the pointing accuracy of the antennas. Knowing the vibration frequencies simplifies the control tasks and may also improve the pointing accuracy. This paper describes identification of vibration frequencies in a space structure, based on frequency weighted Kalman filters, a Gauss-Newton numerical search method and phase-locked loops.